The neutrophil percentage-to-albumin ratio is an independent risk factor for poor prognosis in peritoneal dialysis patients - Mingfan Xu; Jingjia Huan; Lujie Zhu; Jiachun Xu; Kai Song (Renal Failure)
Aim This study aimed to investigate the predictive ability of the neutrophil percentage-to-albumin Ratio (NPAR) concerning all-cause mortality and cardio-cerebrovascular mortality in patients undergoing peritoneal dialysis (PD).Methods We included a total of 807 PD patients from the Peritoneal Dialysis Center of the Second Affiliated Hospital of Soochow University between January 2009 and December 2019 in this study. Patients were categorized into three groups based on their baseline NPAR. The Kaplan-Meier method, multivariate Cox proportional hazard model, and Fine-Gray competing risk model were employed to examine the relationship between NPAR level and all-cause mortality and cardio-cerebrovascular mortality among PD patients. Furthermore, the ROC curve and calibration plots were utilized to compare the performance between NPAR and other conventional indicators.Results The mean follow-up period was 38.2 months. A total of 243 (30.1%) patients passed away, with 128 (52.7%) succumbing to cardio-cerebrovascular diseases. The mortality rates of the Middle and High NPAR groups were significantly greater than that of the Low NPAR group (p < 0.001), and NPAR was independently associated with all-cause mortality and cardio-cerebrovascular mortality. Receiver Operating Characteristic (ROC) analysis indicated that the Area Under the Curve (AUC) of NPAR (0.714) was significantly superior to those of C-reactive protein (CRP) (0.597), neutrophil to lymphocyte ratio (NLR) (0.589), C-reactive protein to albumin ratio (CAR) (0.698) and platelet to lymphocyte ratio (PLR) (0.533).Conclusion NPAR served as an independent predictive marker for all-cause mortality and cardio-cerebrovascular mortality in PD patients. Moreover, NPAR demonstrated superior predictive potential compared to CRP, CAR, NLR, and PLR.